SELECTIVE CATALYTIC OXIDATION AND STEAM OXYGEN CONVERSION OF METHANE INTO SYNTHESIS GAS - Sarsenova R.О.,; Ilyassova О.,; Zhang Х.,; Abdishaki K.,; Kassymbekova D.А.,; Zhangozhina E.N.,; Tungatarova S.A.,; Baizhumanova T.S., (Academic Scientific Journal of Chemistry, 2020)
The results of the stability study of the developed dispersed optimal composition Pt-Ru = 1 : 1 (Pt: Ru = 0.7 : 0.3, at.% ) of the catalyst in the reaction of selective catalytic oxidation (SCO) and steam oxygen conversion (SOC) of methane into synthesis gas at millisecond contact times are presented. Methods of catalyst regeneration were determined. During the study of the stability of a low-percentage granular sample of 1.0% Pt-Ru/2% Ce/(θ+α)Al2O3 catalytic system in the process of oxidation of methane, regeneration methods were found that allow stable conduct of the process of SCO and SOC of methane for 410 hours. As a result of the process, a synthesis gas was obtained with a ratio of H2/CO = 2.0 without the formation of CO2, which is most suitable for its use in the Fischer-Tropsch synthesis of methanol and hydrocarbons. It is assumed that the reaction of SCO of CH4 proceeds by a direct mechanism involving reduced Pt0 , Ru0 and Pt-Ru nanoclusters detected by TEM research after testing the stability of the developed Pt: Ru (1:1) catalyst on a carrier.